Measurements of reflection coefficients of stratified layers using X-band bistatic scatterometers - Jha, K.K.; Singh, K.P.; Singh, R.N. (Springer India, 1984)
Laboratory modelling of earth's subsurface stratification has been carried out using X-band microwave bistatic scatterometer system. Look angle variation of reflectivity for various subsurface layers under dry and wet conditions have been measured. From measured reflectivity data and the reciprocity theorem the emissivity and the brightness temperature variations have been computed, and the data are in good agreement with reported results. The importance of laboratory and field measurements and its remote sensing application has been discussed. © 1984 Indian Academy of Sciences.
Keywords: Bistatic scatterometer; brightness temperature; reflectivity; remote sensing